Factors associated with mortality from external causes in an Intensive Care Unit - Rodrigues de Araújo, Deisiane; da Silva Oliveira, Juliana; Souza de Jesus, Cleber; Sales Vieira, Sheylla Nayara; Pereira Ribeiro, Valéria (O Mundo da Saúde, 2022)
The demographic and epidemiological profile of mortality in Brazil is marked by an increasing number of external causes, which generates a financial impact for the Unified Health System due to the increase in hospital admissions, especially in Intensive Care Units. This study aimed to analyze the factors associated with mortality from external causes in an intensive care unit. This is a cross-sectional survey, based on secondary data, carried out in an Intensive Care Unit in 2019. The data were analyzed using descriptive statistics, to verify the factors associated with hospital mortality, the Qui-squared and Pearson's tests were used. There were 267 (26.72%) admissions to the Intensive Care Unit, of which 49 (18.4%) died. There was an association of death with the variables: sex (p=0.003), age group (p<0.001), city of residence (p=0.041), nature of the injury (p=0.005), affected body region (p=0.023 ), length of stay in the ICU (p=0.024), time to ICU admission (p<0.001), Glasgow Coma Scale (GCS) (p<0.001), Richmond Agitation Sedation Scale (p=0.021), invasive mechanical ventilation (p<0.001), duration of invasive mechanical ventilation (p<0.001), vasoactive drugs (p<0.001), acute kidney failure (p = 0.002), indwelling urinary catheter (p<0.001), gastric tube (p<0.001), central venous catheter (p<0.001), and invasive blood pressure (p<0.001). It was identified that the factors associated with mortality from external causes in the ICU are related to the sociodemographic profile, and the characteristics referring to the event and the care provided.